The Joint Collaborations between the International Human Rights Movement (IHRM) Philippines and Igniting Young Minds (IDYM) Philippines, Pachyderm Tales India in attaining its Sustainability, Development and Goals - Amb Dr. Froilan Delute Mobo (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
The Pandemic brought huge problems in the global community not only in the economic sector but also it has a psychological impact to idle individuals who lost their jobs. Amidst the Pandemic Situations there are also helpful groups who are willing to devote and spent their time in conducting Free International Webinars. IDYM Foundation Philippines and in collaboration with the International Human Rights Movement Philippines (IHRM-Phils, Inc) will be conducting series of International Webinars which will tackle about Human Rights, Educational Technology related issues, and Research Related topics that can help our shape up our individuals and make them more productive and think of other ways to survive from the pandemic we are facing right now. The purpose of this study is to strengthen the collaboration between other NGOs or Civil Society Organization in this time of pandemic that we can work together to support our community in other ways such as by giving free webinars that will help shape their futures